(untitled) (Research, Society and Development, 2021)
Vegetable contamination can happen in several processes, from irrigation, fertilization, collection, transportation, storage, marketing and even contamination triggered by the hands of manipulators and consumers. To minimize and / or cancel this contamination, it is necessary to adhere to measures that improve the hygiene of the vegetable. In this study 27 samples of lettuce were used, defoliated manually and divided into control, treated with vinegar and treated with chlorine. For parasitological analysis, the spontaneous sedimentation method was used. The Microsoft Excel 10 programs were used for descriptive statistical analysis and the Bioetat 5.0 program was used for inferential statistical analysis (p≤ 0.05). All samples were positive for some type of parasitosis in different stages and degrees of parasite. Of the 27 samples, 85.71% had parasites, 67.85% with potentially parasitic organisms and 100% of them had free-living organisms. The vegetables with the highest degree of parasite were those from the fair, with 36.95% of parasitic organisms. Regarding the treatments used, a greater number of parasites were found in the vinegar, suggesting that more organisms were detached from the vegetable, making it suitable for consumption.